Racial disparity in head and neck cancer. Issue 15 (2nd April 2021) - Thomas, Giovana R.
Abstract : Health care disparity in cancer is a well‐recognized entity that is still poorly understood. Disparities in head and neck cancer outcomes for African Americans in the United States have been documented. Access to care is a targetable area of research and interventions to lessen health care disparities in head and neck cancer for our most vulnerable populations.